Comparative study of the impact of dietary supplementation with different types of CpG oligodeoxynucleotides (CpG ODNs) on enhancing intestinal microbiota diversity, antioxidant capacity, and immune-related gene expression profiles in Pacific white shrimp (Litopenaeus vannamei) - Hu, Feng; Wang, Yan; Hu, Jingjie; Bao, Zhenmin; Wang, Mengqiang (Frontiers in Immunology, 2023)
The CpG oligodeoxynucleotides (CpG ODNs) reportedly possess the capacity of strengthening immunity in mammal. This experiment was conducted to evaluate the effects of 17 types of CpG ODNs on intestinal microbiota diversity, antioxidant capacity, and immune-related genes expression of the shrimp Litopenaeus vannamei. Diets with 50 mg kg-1 CpG ODNs wrapped in egg whites were prepared and divided into 17 different groups, while there were 2 control groups (normal feed and feed with egg whites). These CpG ODNs supplemented diets and the control ones were fed to L. vannamei (5.0 ± 0.5 g) with three times daily at 5%-8% shrimp body weight for three weeks. The results of consecutive detection of intestinal microbiota by 16S rDNA sequencing indicated that 11 of the 17 types of CpG ODNs could significantly enhance intestinal microbiota diversity, the populations of several probiotic bacteria and activate possible mechanisms relevant to diseases. The immune-related genes expression and antioxidant capacity in hepatopancreas further proved that the 11 types of CpG ODNs could effectively improve the innate immunity of shrimp. And histology results showed that all CpG ODNs in the experiment did not damage tissue structure of hepatopancreas. The present results suggested that CpG ODNs could be used as trace supplement to improve intestinal health and immunity of shrimp.